Role of ambulance response times in the survival of patients with out-of-hospital cardiac arrest. Issue 8 (25th August 2010) - O'Keeffe, Colin; Nicholl, Jon; Turner, Janette; Goodacre, Steve
Abstract : Objectives: To evaluate the role of ambulance response times in improving survival for out-of-hospital cardiac arrest (OHCA). Methods: OHCAs were identified by sampling consecutive life-threatening category A emergency ambulance calls on an annual basis for the 5 years 1996/7–2000/1 from four ambulance services in England. From these, all calls where an ambulance arrived at the scene and treated or transported a patient were included in the study. These cohorts of patients were followed up to discharge from hospital. Results: Overall, 30 (2.6%) of the 1161 patients with cardiac arrest survived to hospital discharge. If the patient arrested while the paramedics were on scene, survival to hospital discharge was 14%. The most important predictive factors for survival were response time, initial presenting heart rhythm in ventricular fibrillation and whether the arrest was witnessed. The estimated effect of a 1 min reduction in response time was to improve the odds of survival by 24% (95% CI 4% to 48%). The costs of reducing response times across the board by 1 min at the time of this study were estimated at around £54 million. Conclusions: The arrival of a crew prior to OHCA means that the chance of surviving the arrest increases sevenfold. Overall it is possible that rapid response to patients in immediate risk of arrest may be at least as beneficial as rapid response to those who have arrested. Concentrating resources on reducing response times across the board to improve survival for those patients already in arrest is unlikely to be a cost-effective option to the UK National Health Service.